Contextual perceived group threat and radical right-wing populist party preferences: Evidence from Switzerland. (1st March 2016) - Berning, Carl C.
Existing studies suggest that perceived group threat is an important influence on radical right-wing populist party preferences. However, most have focused on perceived group threat at the individual level, overlooking the ideological climate. I examine how an ideological climate of group threat perception as a contextual factor can shape individual preferences for radical right-wing populist party preferences. I argue that above and beyond personal perceived group threat, the prevalence of local perceived group threat exerts a normative influence on personal preferences. Using voting preferences for the Swiss People's Party, I employ multilevel structural equation modeling to examine the theoretical model. I find clear evidence for a contextual effect of perceived group threat on individual-level Swiss People's Party preferences.